Experimental Torsional Capacity of Plain Concrete Beams Made from Crushed Clay Brick and Recycled Brick Concrete as Coarse Aggregate - Md. Ashraful Alam; Syed Ishtiaq Ahmad (Advances in Civil Engineering)
Concrete was made with four different types of coarse aggregate, i.e., natural stone aggregate concrete (NSAC), crushed virgin clay brick aggregate concrete (VBAC), crushed recycled brick concrete aggregate concrete (RBAC), and crushed recycled stone concrete aggregate concrete (RSAC). Beam specimens prepared from these four types of concrete were subjected to pure torsional moment up to failure. From this experimental procedure, ultimate torque at failure along with twisting angle were observed. From the torque vs. twisting angle curves, torsional stiffness and torsional toughness were also evaluated for these four types of concrete. It was observed that ultimate torque of VBAC and RBAC was 95% and 90% of that of NSAC, respectively. The torsional toughness of VBAC was found to be 68%–72% of that of NSAC. In addition, experimental torques were compared with predictions of torsional strength as per five commonly used models. For VBAC, the ultimate torque prediction made by skew bending theory was found to be the closest to the experimental findings.